The Role of Job Happiness in Achieving Workplace Embeddedness An Applied Study on Administrative Staff at King Khalid University - zeyada, Rania Mohamed Mahmoud; Alshehri, Dawlah Abdullah (Dirasat: Human and Social Sciences, 2026)
Objectives: The aim of the research was to evaluate the actual practices of the dimensions of job happiness and embeddedness in the workplace, as well as to study and analyze the extent to which job happiness contributes to supporting embeddedness at King Khalid University. Methods: The research adopted a descriptive-analytical approach using a sample of employees at King Khalid University. An electronic questionnaire was designed to collect the data, and the study sample consisted of 297 individuals. Results: Lack of clarity of the concept of job happiness and the mechanisms of its application The study sample does not agree on the availability of implantation dimensions in the workplace There is a strong statistically significant direct correlation between job happiness as an independent variable and workplace immersion as a dependent variable The correlation was stronger for the dimension of sacrifice from the two dimensions, harmonization and links. Conclusions: The following recommendations were reached: the importance of enhancing factors that contribute to job happiness, such as job satisfaction and organizational justice, improving the perceived organizational support, creating a supportive work environment for thinking and constructive initiatives, and enhancing the social connections among employees.